Molecular diagnosis of kidney transplant failure based on urine - Wiesener, Antje; Morath, Christian (American journal of transplantation, 2020)
In light of the organ shortage, there is a great responsibility to assess postmortal organs for which procurement has been consented and to increase the life span of transplanted organs. The former responsibility has moved many centers to accept extended criteria organs. The latter responsibility requires an exact diagnosis and, if possible, omission of the harmful influence on the transplant. We report the course of a kidney transplant that showed a steady decline of function over a decade, displaying numerous cysts of different sizes. Clinical workup excluded the most frequent causes of chronic transplant failure. The filed allocation documents mentioned the donor’s disease of oral-facial-digital syndrome, a rare ciliopathy, which can also affect the kidney. Molecular diagnosis was performed by culturing donor tubular cells from the recipient´s urine more than 10 years after transplantation. Next-generation panel sequencing with DNA from tubular urinary cells revealed a novel truncating mutation in OFD1, which sufficiently explains the features of the kidney transplants, also found in the second kidney allograft. Despite this severe donor disease, lifesaving transplantation with good long-term outcome was enabled for 5 recipients.
First published: 09 December 2019
Correction added on 6 March 2020, after first online publication: The copyright line has been updated
Gesehen am 22.04.2020